2013
DOI: 10.1371/journal.pone.0083732
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Role of Cell-Surface Molecules in Central Synaptogenesis in the Drosophila Visual System

Abstract: A hallmark of the central nervous system is its spatial and functional organization in synaptic layers. During neuronal development, axons form transient contacts with potential post-synaptic elements and establish synapses with appropriate partners at specific layers. These processes are regulated by synaptic cell-adhesion molecules. In the Drosophila visual system, R7 and R8 photoreceptor subtypes target distinct layers and form en passant pre-synaptic terminals at stereotypic loci of the axonal shaft. A leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…To visualize yR7 terminals, we used the active zone reporter line Rh4-LexA ::p65 , 8XLexAop2-Brp-short mCherry ( Rh4>Brp-short mCherry )(Berger-Muller et al, 2013). Bruchpilot (Brp) is an obligate active zone component at most or all synapses, and Brp-short mCherry is a truncated form of Brp that labels existing active zones by associating with full-length Brp but cannot create new active zones when overexpressed (Berger-Muller et al, 2013; Fouquet et al, 2009). In adults heterozygous for dpr11 MiMIC or DIP-γ MiMIC , yR7 terminals labeled by Brp-short mCherry were bulb-shaped and regularly arranged in M6 (Figures 7A, C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To visualize yR7 terminals, we used the active zone reporter line Rh4-LexA ::p65 , 8XLexAop2-Brp-short mCherry ( Rh4>Brp-short mCherry )(Berger-Muller et al, 2013). Bruchpilot (Brp) is an obligate active zone component at most or all synapses, and Brp-short mCherry is a truncated form of Brp that labels existing active zones by associating with full-length Brp but cannot create new active zones when overexpressed (Berger-Muller et al, 2013; Fouquet et al, 2009). In adults heterozygous for dpr11 MiMIC or DIP-γ MiMIC , yR7 terminals labeled by Brp-short mCherry were bulb-shaped and regularly arranged in M6 (Figures 7A, C).…”
Section: Resultsmentioning
confidence: 99%
“…To examine whether formation of synapses between yR7s and Dm8s involves interactions between Dpr11 and DIP-γ, we expressed a marker for existing active zones, Brp-short mCherry , in yR7s (Berger-Muller et al, 2013; Fouquet et al, 2009). In control animals, yR7 terminals are bulb-shaped and regularly arranged in M6.…”
Section: Discussionmentioning
confidence: 99%
“…R7 terminates in the deeper M6 layer, whereas R8 terminates in the M3 layer. The synapse can be visualized by a molecular marker fusing active zone component Bruchpilot (Brp) and mCherry (Berger-Muller et al, 2013;Fouquet et al, 2009;Sugie et al, 2015) or GFP (Chen et al, 2014).…”
mentioning
confidence: 99%
“…To knock down bdl in postsynaptic targets of R8, ort C1-3 -GAL4 (Gao et al, 2008) was used to drive the expression of UAS-bdl-RNAi. The lexA/lexAop system was used to label SV components in bdl knockdown flies; the SV marker lexAop-nSyb-spGFP1-10 (Macpherson et al, 2015), was expressed under control of the greensensitive-R8-specific driver Rh6-lexA::p65 (Berger-Müller et al, 2013). We found that knocking down bdl in postsynaptic targets of R8 caused a similar SV mislocalization phenotype in all individuals examined (100%, n ϭ 4 animals; (Fig.…”
Section: Knocking Down Bdl In Postsynaptic Target Neurons In the Optimentioning
confidence: 69%